Mary Johnson of Wethersfield, Connecticut, hanged for witchcraft, 1648 (poem) - Shipley, Vivian (Connecticut Literary Anthology: Celebrating Nutmeg Authors, 2020, 2020)
Connecticut Literary Anthology features thirty-six Connecticut poets and prose writers from across the Nutmeg State. The 2020 Anthology is published by the Central Connecticut State University English Department. The writers in the inaugural anthology share themes amplified by current events, but not the context. Stories of family, economic in- equality, sexual violence, social justice, culture wars, lost love, aging, and gender—they’re all in here. And mangoes. Everyone loves mangoes. Featured writers: Janet L. Bannister, Charles V. Belson, Susan Cinoman, Ginny Lowe Connors, Jason Courtmanche, Catherine DeNunzio, Joanie DiMartino, Catherine DeNunzio, Meghan Evans, Maura Faulise, Kathryn Fitzpatrick, Beth Gibbs, Cecilia Gigliotti, Nichole Gleisner, Sitara Gnanaguru, Emi Gonzalez, José B. González, Benjamin S. Grossberg, Avery Jenkins, B. Fulton Jennes, Sarah Darer Littman, Kiran Masroor, Melissa McEwen, Claudia McGhee, Nancy McMillan, Jean P. Moore, Steven Ostrowski, Makenzie Ozycz, Aimee Pozorski, Kara Molway Russell, Vivian Shipley, Amy Sisson, Katherine A. Szpekman, Wendy Terry, Mika Taylor, Marina Tinone, Jason Wilkins. Praise for Anthology: "It feels like we have become unglued from one another since March of 2020; masked strangers passing each other in anonymity. But this anthology glues us back together and helps us find ways to heal and talk with one another. Important stories are told, and we should heed them." —Lisa Comstock, Director for Connecticut Center for the Book
Keywords: dept.eng